2023
DOI: 10.3389/fcimb.2023.1139998
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key genes related to inflammasome in severe COVID-19 patients based on a joint model with random forest and artificial neural network

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) has been spreading astonishingly and caused catastrophic losses worldwide. The high mortality of severe COVID-19 patients is an serious problem that needs to be solved urgently. However, the biomarkers and fundamental pathological mechanisms of severe COVID-19 are poorly understood. The aims of this study was to explore key genes related to inflammasome in severe COVID-19 and their potential molecular mechanisms using random forest and artificial neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[ 48 ] MKI67 is associated with the activation of the NLRP3 inflammasome and can be used as a potential marker to identify patients with severe COVID-19. [ 49 ] KIF4A is a protein-coding gene that encodes a kinesin family motor protein essential for chromosome condensation, segregation, and cytokinesis during cell division, thereby maintaining genomic stability. [ 50 ] Reduced H3K27me3 modification at the KIF4A promoter sequence and decreased expression of the zeste cognate-2 enhancer (EZH2) increase KIF4A expression, contributing to the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] MKI67 is associated with the activation of the NLRP3 inflammasome and can be used as a potential marker to identify patients with severe COVID-19. [ 49 ] KIF4A is a protein-coding gene that encodes a kinesin family motor protein essential for chromosome condensation, segregation, and cytokinesis during cell division, thereby maintaining genomic stability. [ 50 ] Reduced H3K27me3 modification at the KIF4A promoter sequence and decreased expression of the zeste cognate-2 enhancer (EZH2) increase KIF4A expression, contributing to the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GNG11 plays a key role in heart rhythm regulation and is associated with cardiac disease risk [ 103 ]. The CDKN3 gene could be used as a potential marker to identify severe COVID-19 patients [ 104 ]. Yue et al [ 105 ] identified 10 central genes, including CDKN3, and stated that these genes may serve as new target markers for early diagnosis, prognosis and therapy in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN3 is a member of the protein kinase family and is thought to play an important role in the cell cycle regulatory pathway 4,5 . CDKN3 was found to have roles in cell cycle progression regulation [6][7][8][9] , human vascular endothelial cells 10 , severe COVID-19 11 , female genotoxicity 12 , vascular endothelial cell injury 13 , control of mitosis 14 , and promotion of preadipocyte proliferation 15 . Interestingly, CDKN3 has also been shown to be involved in tumor progression.…”
Section: Introductionmentioning
confidence: 99%